[Bean Caointe or Keener] - Timbrell, James Christopher, Artist, 1810-1850; Hall, S. C., Mrs., 1800-1881 (1840)
Portrait of a Bean Caointe or Keener at work at a wake.
Attributed to James Christopher Timbrell.
Catalogue of Irish Topographical Prints and Original Drawings / Rosalind M. Elmes ; New edition revised and enlarged by Michael Hewson - Dublin : Malton Press, 1975
Ireland: its scenery, character, &c / Mr. & Mrs. S. C. Hall - London: How and Parsons, 1841-43
Keywords: Wake services -- Ireland -- 1830-1840; Women -- Ireland -- 1830-1840; Pencil drawings -- Irish -- 1830-1840.